THE INFLUENCE OF QUALITY OF WORK LIFE ON EMPLOYEE PERFORMANCE AT CLASS IIA WOMEN’S PRISON BANDAR LAMPUNG - Rachmayanthy, Rachmayanthy; Elyus, Nikita RM (Universitas Nusa Cendana, 2025)
This study aims to analyze the influence of quality of work life on employee performance at the Class IIA Women's Prison in Bandar Lampung. In this era of digitalization could be increasing the competitive level and demands in organizations, it makes the transformation of human resources is crucial to ensure optimal employee performance and maximum achievement of organizational goals. This study used a descriptive quantitative approach with a cross-sectional survey design. Data were collected from 73 respondents obtained from the Krejcie and Morgan table, while data collection was carried out using simple random sampling techniques. The results of this study are the quality of work life has a positive and significant influence on employee performance at the Class IIA Women's Prison in Bandar Lampung. This study concludes that the quality of work life is an important factor affecting employee performance. Therefore, improving the quality of work life through various initiatives and programs can be an effective strategy to improve employee performance in a competitive and demanding work environment such as the Class IIA Women's Prison in Bandar Lampung. Keywords: Quality of Work Life; Employee Performance; Prisons